Phosphorus and zinc uptake and protein, lysine and tryptophane contents in quality protein maize in relation to phosphorus and zinc fertilization in mollisol - Jangir, Abhishek; Singh, Veer; Srivastava, P.C.; Ram, Shri; Bhatnagar, Amit (Annals of Agricultural Research, 2016)
High quality protein maize hybrid HQPM-1 grown with different doses of phosphorus (0, 30, 60 and 90 kg/ha) and zinc (0, 5, 10 and 15 kg/ha) to evaluate the effect of P and Zn on their uptake, plant growth, grain yield and protein quality during kharif season 2012 on zinc deficient silty clay loam soil. Application of P and Zn significantly increased the available P in soil however; available Zn reduced with increment of P. There was gradual increase in plant height, ear height, number of leaves and test weight with increase in P and Zn doses however, root dry weight decreased beyond 60 kg P and 10 kg Zn/ha. Application of P up to 60 kg/ha and Zn up to 15 kg/ha reduced the anthesis silking interval. Phosphorus and zinc uptake also increased with increasing P and Zn level upto 60 kg/ha and 15 kg/ha, respectively. The grain and stover yields were significantly affected by P and Zn however; grain yield did not significantly influence due to P and Zn interaction. Phosphorus and zinc application had synergistic impact on protein, lysine and tryptophan content of grain where maximum contents were found with the highest doses of P and Zn.